1976
DOI: 10.3758/bf03213219
|View full text |Cite
|
Sign up to set email alerts
|

Short-term memory limitations in children: Capacity or processing deficits?

Abstract: This paper evaluates the assertion that short-term memory (STM) capacity increases with age. Initially an analysis is made of the STM system in terms of its parameters and control processes. No evidence was found that can suggest conclusively that either the capacity or the rate of information loss from STM varies with age. On the other hand, substantial evidence exists to show that the processing strategies used by adults are unavailable or deficient in children. Furthermore, considerable differences in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
2
12

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(137 citation statements)
references
References 101 publications
(92 reference statements)
6
117
2
12
Order By: Relevance
“…The comparison of memory for consonant sequences that cannot be recoded easily and memory for generally known consonant-vowel sequences was compared. Age differences in memory spanwerein fact very dependent on material type (see also Chi, 1976). Only minimal age differences were found for consonant sequences that could easily be integrated, whereas relatively marked developmental differences were obtained for consonant-vowel sequences.…”
Section: Millermentioning
confidence: 99%
“…The comparison of memory for consonant sequences that cannot be recoded easily and memory for generally known consonant-vowel sequences was compared. Age differences in memory spanwerein fact very dependent on material type (see also Chi, 1976). Only minimal age differences were found for consonant sequences that could easily be integrated, whereas relatively marked developmental differences were obtained for consonant-vowel sequences.…”
Section: Millermentioning
confidence: 99%
“…Instead, performance is determined by subjects' ability to skillfully allocate cognitive resources to the relevant task components (Enns & Brodeur, 1989). Therefore, the poorer performance of younger children is attributable to their use of inadequate strategies in allocating cogmtive resources to task components rather than to their underdeveloped attentional capacity (Chi, 1976;Geffon & Sexton, 1978).…”
Section: Developmentallssues In the Relationsmentioning
confidence: 99%
“…Studies on STM capacity have shown that children can recall fewer symbols than adults (e.g., Chi, 1976;Dempster, 1981;Keating & Bobbitt, 1978). This result could indicate that up to about age 13 or 14, STM capacity increases (e.g., Pascual-Leone, 1989a).…”
Section: Short-term Memorymentioning
confidence: 90%